An orbit maneuver detection method based on orbital elements for BeiDou GEO and IGSO satellites. Issue 10 (15th May 2022) - Fan, Lihong; Tu, Rui; Zhang, Rui; Han, Junqiang; Zhang, Pengfei; Wang, Siyao; Hong, Ju; Lu, Xiaochun
Abstract: In addition to the orbital maneuver information, other satellite anomalies were also marked in the satellite's health status of broadcast ephemeris. For the signal-in-sp ace (SIS) performance evaluation, it is necessary to classify and evaluate the impact of a single fault, as well as the comprehensive impact. Therefore, it remains to identify the satellite orbital maneuver from the broadcast ephemeris and evaluate its impact on the signal-in-space performance. This study proposed an orbit maneuver detection method based on a combination of the square root of the major half-axis of the satellite orbit and the health status of the satellite recorded in broadcast ephemeris. The broadcast ephemerides provided by The Multi-GNSS Experiment (MGEX) from 2016 to 2020 were first used to detect the orbit maneuvers of BeiDou satellites; the orbit maneuvering and recovery periods of GEO and IGSO were detected next. The number of orbital maneuvers of the satellites made each year, and the interval of orbital maneuver of each satellite, was also obtained. The main findings of this study are as follows: (1) the proposed method can detect satellite orbit maneuvers and recovery periods recorded in the broadcast ephemeris; (2) the average orbit maneuvering interval of GEO and IGSO satellites were obtained and found to be approximately 27 days for GEO satellites except C04 and the IGSO, for which they were 45 days and approximately 178 days, respectively; (3) the average recovery time for the two types of satellite orbital maneuvers was about 6.6 h, and generally the same for the BeiDou-3 and BeiDou-2 satellites; and (4) using the detected orbital maneuver intervals and recovery periods, its impact on the signal-in-space availability and continuity of the BeiDou satellite was evaluated, which showed that the per-satellite availability of IGSO satellites were approximately 0.998 and 0.9998/h respectively. The per-satellite availability of each GEO satellite was about 0.986–0.996, and the continuity was about 0.9982/h-0.9992/h; therefore, the orbital maneuver reduced the per-satellite availability and continuity of the GEO and IGSO satellites by 0.002–0.014 and approximately 0.0002/h-0.0018/h, respectively.